The Role of Masjid Youth Organization to Improve Self-Development of Adolescens (Case Study of Masjid Youth Organization in Masjid Jogokariyan (RMJ) Yogyakarta) - Moh Alwi Yusron; Rika Indah Arsita (Educan : Jurnal Pendidikan Islam, 2021)
Adolescences is identical with delinquency, one of the causes is a lack of Self-Development. Self-Development is greatly influenced by the environmental conditions in which a person lives. Youth of Masjid Jogokariyan is one of the youth communities in Yogyakarta which is a forum for teenagers to improve self-development.This study aims to determined how the role of the Youth of Masjid Jogokariyan in improved self-development of adolescents. The role these was explained below which each the component of self development. These component of self-development that are: emotional /knowledge, physical, mental, social, education, and also self develop accordance to market demand. Thus the role was explained below followed by the supporting and inhibiting factors each the component.This study employed qualitative a case study approached and was taken at Yogyakarta Masjid Jogokariyan with descriptive method. The data was collected through interviews, observation and documentation. The data were analyzed applied Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing.Based on the results of the research, the researcher give suggestions to (1) the management of the masjid youth organization to be more and always innovate, improving creativity, and improving skills in the field of information technology (IT), (2) seniors as responsible of masjid youth organization coaches to further increase enthusiasm in guiding organizations to be more involved in the organization, (3) to guardians and families especially the parents of adolescents, member of masjid youth organization to pay more attention to the cultivation and implementation of religious values in adolescents and the quality of the youth friendship environment.